Analisis Pengaruh Tata Kelola Perusahaan Dan Struktur Modal Terhadap Kinerja Perusahaan - Supriyanto Supriyanto; Jhoni Hendri (Universitas Muhammadiyah Malang, 2021)
This paper aims to examine the company's performance problems as measured by book or market value by analyzing the proportion of executive directors, proportion of independent directors, board size, female directors, audit committee meetings, institutional investors, and the company's capital structure. This study uses the company's assets and capital as control variables. The paper object consists of 382 companies excluding the financial sector listed on the Indonesia Stock Exchange from 2016 to 2020. The study used purposive sampling techniques in collecting the research data. Data is processed using multiple regression methods with SPSS and Eviews statistical applications. The results showed that executive directors, independent directors, female directors, audit committee meetings, and institutional investors had no significant effect on ROA or Tobin's Q. While the board size proved to have a significantly positive relationship to Tobin's Q but not significantly related to ROA. On the other hand, the capital structure proved to be significantly negatively associated with ROA but significantly positively related to Tobin's Q.